Focal Staphylococcus Aureus Septic Arthritis Elicits Age and TLR2-Dependent Periarticular Bone Loss - Schultz M; Hu Z; Deshmukh M; Henning P; Lerner UH; Mohammad M; Jin T (Journal of Inflammation Research)
Michelle Schultz,1,* Zhicheng Hu,1,2,* Meghshree Deshmukh,1 Petra Henning,3 Ulf H Lerner,3 Majd Mohammad,1 Tao Jin1,4 1Department of Rheumatology and Inflammation Research, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 2Center for Clinical Laboratories, the Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China; 3Department of Internal Medicine and Clinical Nutrition, Institute of Medicine, Sahlgrenska Osteoporosis Centre and Centre for Bone and Arthritis Research at the Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 4Department of Rheumatology, Sahlgrenska University Hospital, Gothenburg, Sweden*These authors contributed equally to this workCorrespondence: Michelle Schultz, Department of Rheumatology & Inflammation, Institute of Medicine, The Sahlgrenska Academy at the University of Gothenburg, Guldhedsgatan 10A, Gothenburg, 41346, Sweden, Tel +46-31-3426475, Fax +46-31-823925, Email michelle.schultz@gu.seIntroduction: Septic arthritis, primarily caused by Staphylococcus aureus (S. aureus), is a severe joint infection that leads to joint and bone damage. S. aureus lipoproteins (LPPs) bind to Toll-like Receptor 2 (TLR2), inducing arthritis and localized bone loss. Aging affects TLR2 immune response to pathogens. While intra-articular injections of S. aureus LPPs induces local bone resorption in mice, the influence of aging and TLR2 expression on bone mineral density (BMD) after S. aureus bacteremia remains unclear.Methods: We analyzed distal femoral BMD in young and old TLR2 knock-out and wild-type mice following intravenous S. aureus infection. BMD was measured in both total and trabecular bone in old and young mice to determine age and TLR2-dependent responses to infection.Results: In non-infected mice, BMD in both total and trabecular bone was mainly age-related and TLR2-independent. Following S. aureus bacteremia, young wild-type mice with TLR2 expression showed decreased combined cortical and trabecular BMD. This effect was absent in aged mice or TLR2 deficient mice. Focal septic arthritis, induced by S. aureus bacteremia, emerged as the primary cause to bone loss in the femur metaphysis. TLR2 appears to play a crucial role in focal septic arthritis-induced bone loss, as evidenced by in vitro findings demonstrating that staphylococcal LPPs, known TLR2 agonists, increase the Tnfsf11/Tnfrsf11b ratio in mouse pariosteal osteoblasts.Conclusion: S. aureus bacteremia triggers local bone loss in murine arthritis, depending on both age and TLR2 expression.Keywords: septic arthritis, Staphylococcus aureus, aging, TLR2, bone mineral density, mouse